220k views
4 votes
Suppose you're given the formula q = 2o + 6p. If you know that p = o – 7, how could you rewrite the formula?

User LukeSolar
by
5.0k points

2 Answers

5 votes

q = 2o + 6p

p = o – 7

⇒ q = 2o + 6(o - 7) = 2o + 6o - 6 × 7 = 8o - 42

⇒ q = 8o - 42

User Saltern
by
4.6k points
2 votes

Answer:

q = 8o - 42

Explanation:

Given: The given formula is q = 2o + 6p.

p = o – 7

Now we have to plug in p = o - 7 in the given formula, we get

q = 2o + 6(o - 7)

Now we use the distributive property a(b-c) =ab - ac and expand.

q = 2o + 6o -6(7)

q = 2o +6o - 42

Here 2o and 6o are the like terms, we can add them

q = 8o - 42

User Arnaud Potier
by
4.5k points